Company Size, Capital Structure and Cash Flow Against Company Value in Construction Companies Listed on the Indonesia Stock Exchange (IDX): Ukuran Perusahaan, Struktur Modal dan Arus Kas Terhadap Nilai Perusahaan Pada Perusahaan Kontruksi Yang Terdaftar di Bursa Efek Indonesia (BEI) - Chowiyah, Chowiyah; Nurasik, Nurasik (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine whether company size, capital structure and cash flow have an effect on firm value in construction companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2020 period. The method used is quantitative. In this study, the type of data used was secondary data with data collection techniques using the documentation method, as well as sampling using the purposive sampling method. Population data as many as 16 companies, and obtained a sample of 8 companies. in this study using SPSS. The results of this study are firm size has no significant effect on firm value, capital structure has no significant effect on firm value, cash flow has no significant effect on firm value.